2016
DOI: 10.4103/0973-1075.185028
|View full text |Cite
|
Sign up to set email alerts
|

Integration of early specialist palliative care in cancer care and patient related outcomes: A critical review of evidence

Abstract: Introduction:World Health Organization and American Society of Clinical Oncology recommend early integration of specialist palliative care in patients with cancer. This paper focuses on critical review of evidence on integration of early specialist palliative care in cancer care and patient-related outcomes.Methods:The question for the literature search was – Does integration of early specialist palliative care in cancer care influences patient-related outcomes? 31 articles related to literature search review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 40 publications
0
27
1
1
Order By: Relevance
“…[162][163][164][165][166][167][168][169][170][171][172] Oncologists' end of life care attitudes can influence their timely palliative care referral and end of life cancer treatment decisions. There is evidence that oncologists often refer patients late in the course of illness, 166,167,[173][174][175][176] despite believing, as found in recent surveys, that integration of early specialist palliative care in cancer improves symptom control, end-of-life care, health-related communication, and continuity of care. 173,176 A survey of 182 oncologists in the USA from a major cancer centre, found that comfort with the concepts of end of life care was associated with higher rates of specialist palliative care referral and self-reported primary palliative care delivery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[162][163][164][165][166][167][168][169][170][171][172] Oncologists' end of life care attitudes can influence their timely palliative care referral and end of life cancer treatment decisions. There is evidence that oncologists often refer patients late in the course of illness, 166,167,[173][174][175][176] despite believing, as found in recent surveys, that integration of early specialist palliative care in cancer improves symptom control, end-of-life care, health-related communication, and continuity of care. 173,176 A survey of 182 oncologists in the USA from a major cancer centre, found that comfort with the concepts of end of life care was associated with higher rates of specialist palliative care referral and self-reported primary palliative care delivery.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that oncologists often refer patients late in the course of illness, 166,167,[173][174][175][176] despite believing, as found in recent surveys, that integration of early specialist palliative care in cancer improves symptom control, end-of-life care, health-related communication, and continuity of care. 173,176 A survey of 182 oncologists in the USA from a major cancer centre, found that comfort with the concepts of end of life care was associated with higher rates of specialist palliative care referral and self-reported primary palliative care delivery. 177 A recent systematic review found that the concepts of integration were varyingly defined.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Thus, the American Society of Clinical Oncology has recommended that "combined standard oncology care and palliative care should be considered early in the course of illness for any patient with metastatic cancer and/or high symptom burden." 1(p880) In addition, to improve the overall management of distress in patients with cancer, the National Comprehensive Cancer Network has recommended that all patients be screened throughout the trajectory of their disease course.…”
Section: Introductionmentioning
confidence: 99%
“…Yet this model fails in low-resource settings where the alternative is no care. The potential benefit palliative care can offer patients, their children, grandchildren and local economy lies in mitigation of the costs of illness and suffering, rather than avoidance of costs of expensive treatment 25. On a societal level, palliative care can serve as a health system expander in offering patients with incurable disease the possibility of care within their homes, thereby reserving hospital-based care, with its limited resource of nurses, doctors and supplies for patients with potentially reversible illness.…”
mentioning
confidence: 99%